2023
DOI: 10.3390/bioengineering10040449
|View full text |Cite
|
Sign up to set email alerts
|

Human-Derived Cortical Neurospheroids Coupled to Passive, High-Density and 3D MEAs: A Valid Platform for Functional Tests

Abstract: With the advent of human-induced pluripotent stem cells (hiPSCs) and differentiation protocols, methods to create in-vitro human-derived neuronal networks have been proposed. Although monolayer cultures represent a valid model, adding three-dimensionality (3D) would make them more representative of an in-vivo environment. Thus, human-derived 3D structures are becoming increasingly used for in-vitro disease modeling. Achieving control over the final cell composition and investigating the exhibited electrophysio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 143 publications
1
0
0
Order By: Relevance
“…Since we can detect action potentials within a very short time (sometimes only several minutes) after tissue placement, we can therefore select tissues which are responding and rapidly discard non-active 3D neural tissues before starting long-term experiments. During the validation process of this new approach, we analyzed different parameters to describe the general neuronal activity, synchronicity, as well as burst structures of multiple spike trains to confirm that the functionality of neural tissues was similar to previous works using different types of MEA devices ( Muzzi et al, 2023 ). In addition, the “embedded” configuration could allow chimeric assemblies which may be of interest, i.e., different tissues being positioned on either side.…”
Section: Discussionsupporting
confidence: 54%
“…Since we can detect action potentials within a very short time (sometimes only several minutes) after tissue placement, we can therefore select tissues which are responding and rapidly discard non-active 3D neural tissues before starting long-term experiments. During the validation process of this new approach, we analyzed different parameters to describe the general neuronal activity, synchronicity, as well as burst structures of multiple spike trains to confirm that the functionality of neural tissues was similar to previous works using different types of MEA devices ( Muzzi et al, 2023 ). In addition, the “embedded” configuration could allow chimeric assemblies which may be of interest, i.e., different tissues being positioned on either side.…”
Section: Discussionsupporting
confidence: 54%
“…To circumvent these challenges, innovative 3D MEA configurations have been developed to enable more comprehensive activity measurements within organoids ( Choi et al., 2021 ; Shin et al., 2021 ). Comparative studies of organoids on 2D low-density (8x8), 3D low-density (8x8), and 2D high-density (64x64) MEA have shown that 2D high-density MEA are more adept at detecting activity within organoids ( Muzzi et al., 2023 ), suggesting that higher electrode density may offer better suitability for organoid recordings. Emerging MEA platforms, such as mesh nanoelectronics and organoid-integrating scaffolds, promise to facilitate 3D and high-resolution recordings within cortical organoids ( Huang et al., 2022a ; Liu et al., 2020 ; Passaro and Stice, 2020 ; Yang et al., 2024 ).…”
Section: Functional Measurementsmentioning
confidence: 99%